Protótipo de uma plataforma web para locação de imóveis na cidade de Mãe do Rio - PA (Clickasa) - QUADROS, Osvaldo Filho Fernandes de (2024)
Housing for rent is an alternative for those who wish or need a new home, but do not have the purchasing power to acquire their own house. In addition, renting is a more flexible option for those who do not intend to stay in a specific location for a long time. Many startups that work in the real estate market, such as ZAP Aluguel, QuintoAndar, and Imovelweb, are investing in new tools that assist the rental process. However, there are few options for renting properties in small cities, such as the city of Mãe do Rio, in Pará, which has approximately 30,389 inhabitants. With this problem in mind, the work proposes a prototype of a specific web platform (Clickasa) for people who want to search for housing in the Mãe do Rio region - PA. The platform will be free and will generate profits through ads on the page. For this work, requirements (functional and non-functional), use case diagrams, activity diagrams, sequence diagrams, and the prototyping of the web platform were carried out. The Tenant user can search for rental properties according to the desired category. The Landlord user can offer their properties to be available for rent.